An analysis of pharmaceutical care for critical patients of an adult Intensive Care Unit - Maurício Fábio Gomes; Camilo Molino Guidoni (Universidade de São Paulo, 2023)
Abstract This work analyzed the pharmacotherapeutic problems identified by the clinical pharmacist in an intensive care unit (ICU) and the acceptance of pharmaceutical interventions in solving these problems. This is a descriptive cross-sectional retrospective study, carried out in the adult ICU of a public hospital. All patients hospitalized during the study period had their pharmacotherapy monitored and those whose stay at the ICU lasted less than 24 hours were excluded. The pharmacotherapeutic problems were classified according to type, cause, acceptability/implementation, mode of intervention, outcome and related pharmacotherapeutic group. 302 patients were followed up and 350 pharmacotherapeutic problems were identified. Most of them were classified as unnecessary drug-treatment (n=186; 53.1%). The most frequent causes were excessive drug administration (n=181; 97.3%), and antimicrobials was the main group of drugs associated to that type of problem. 350 pharmaceutical interventions were performed, highlighting "prescriber informed only" (n=178; 50.9%), with an average acceptability of 90.7%, with those carried out on site being more effective (93.4%). The number of pharmacotherapeutic problems that were totally solved was 282 (80.6%). Clinical pharmacy activities in the ICU identified, prevented and corrected pharmacotherapeutic problems, contributing to the optimization of pharmacotherapy in aspects related to the need, efficacy and safety of treatments.